G571(P) Do all neonatal admissions need hospital follow up? – A Tertiary unit experience. (27th April 2016) - Tamilselvan, K; Opute, A; Murthy, V
Abstract : Context/problem: The duration of admissions to a neonatal unit for medical care are varied and is based on the severity of the illness. Currently, there is no consensus on which infants need hospital based follow up. Infants admitted to our neonatal unit, automatically received a routine hospital based neonatal follow up, irrespective of the duration of stay or severity of the clinical problem. We hypothesised that a significant proportion of infants may not need hospital based neonatal follow up. We aimed to identify those admissions in which a hospital based follow up may not be essential. Assessment of problem and analysis of its causes: A qualitative questionnaire was designed to capture the details of the medical indication for hospital based follow up. This included details of gestational age, birth weight, congenital anomalies and other medical reasons including discussion of imaging and blood test results. Furthermore, the clinician's opinion whether the appointment was necessary was also sought. Study Design: This was a prospective data collection over one month period. The clinicians responsible for conducting the clinic filled the questionnaire immediately after each follow up appointment. The completed questionnaires were analysed at the end of each clinic and missing details were entered by reviewing the notes or by a face to face interview of the clinician conducting the clinic. The data was entered into a database for analysis. Results: Fifty questionnaires were analysed for this study. Consultants completed 36/50 (72%) responses and the remaining responses were completed by the junior doctors. The clinicians classified 21/50 (42%) of the appointments as "routine appointments" due to admission to the neonatal or transitional care unit excluding the appointments due to prematurity. In 7/50 (14%) of the appointments the primary reason was to discuss the blood results/imaging reports, clinicians identified that in 5/7 (71.4%) the results could have been done as a phone consultation or via a letter to the carers. In infants born greater than 33 weeks of gestation 6/7 (85.7%) were discharged following the first clinic appointment. This raised the question as to whether the appointment was deemed necessary in the first instance. Measurement of Improvement: Infants who needed brief admissions to the neonatal unit and awaiting blood or imaging reports will not routinely need neonatal clinic follow up. A discharge consultation with a senior member of the medical team and a letter to the parent/carers and GP should be sufficient. A pathway for neonatal follow up appointments has been established following this project. The recommendation is to not routinely offer clinic appointments for all admissions to the neonatal unit. For infants admitted to neonatal unit for less than 48 h, a follow up appointment is to be offered only if the attending consultant deemed it necessary. Infants born more than 33 weeks of gestation should not be offered routine follow up unless associated with other comorbidities. Results of blood tests and imaging should be communicated either over a phone consultation or via a letter to carers and GP. The change in practice is being implemented and a re-audit scheduled to review the effect of the change. Conclusion and lessons learnt: Routine follow up of all infants admitted to the neonatal unit is not necessary. Clear guidance and further discussions with a senior medical colleague prior to discharge can improve the efficiency, quality and patient satisfaction. Furthermore, repeated evaluation and developing strategies may help in delivering a cost effective hospital based follow up clinic.